Implementation of Entrepreneurship MBKM: Application of Automatic Embroidery Machine Technology as a Competitiveness of Embroidery Convection Business at Indah Collection Embroidery Convection - Handika Bayu Alfarris; Koerniawan Hidayat (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The implementation of automatic embroidery machines is an alternative that can increase the effectiveness and efficiency of the production process carried out by the Indah Collection Embroidery Convection. In practice, it discusses the application of automatic embroidery machine technology and the competitiveness of the Indah Collection Embroidery Convection business. This implementation method is video-based and discusses the application of machine embroidery technology. The application of an automatic embroidery machine is divided into several stages: the initial stage, the production stage, and the finishing stage. The results of the discussion found that the application of automatic embroidery machine technology is more widely used than manual embroidery machines and raises the competitiveness of embroidery convection businesses using both automatic and manual embroidery machines.